Death at the alma mater - Malliet, G. M., 1951- (Malliet, G. M., 1951- St. Just mystery, 2010)
St. Michael's College, Cambridge, is prestigious, stately, and in frightful disrepair. To replenish the college's dwindling coffers, the Master holds a fundraising weekend for wealthy alums. But all goes awry when Lexy Laurant is found viciously strangled to death. Gorgeous and successful, Lexy inspired jealousy, envy, and spite in everyone. There's a lengthy list of likely suspects: Lexy's debt-ridden Latino lover, her novelist ex-husband who jilted her, and a hot-tempered Texan once rejected by the victim, among others. As Detective Chief Inspector St. Just weighs clashing egos, he discovers unsavory secrets, and a most shocking twist.